Diagnostic Value of Stress Radiography and Arthrometer Measurement for Anterior Instability in Anterior Cruciate Ligament Injured Knees at Different Knee Flexion Position - Lee, Han-Jun; Park, Yong-Beom; Kim, Seong Hwan (Arthroscopy, 2019)
To evaluate diagnostic value of stress radiography and arthrometer measurements for anterior instability at different knee flexion angle positions. Forty-three patients with complete anterior cruciate ligament (ACL) rupture (group 1) and 37 normal subjects (group 2) were enrolled prospectively. Arthrometer (KT-1000) measurements and stress radiography by Telos were used to evaluate side-to-side differences. Results were recorded according to the knee position (30°, 45°, 60°, and 90°). Areas under the receiver operating characteristic curves (AUCs) were used to evaluate the diagnostic accuracy of each evaluation method. The calculated cutoff values at 30° position were used to evaluate the sensitivity and specificity of combined evaluation with stress radiography and arthrometer measurements. The side-to-side differences on stress radiography and arthrometer measurements were significantly different between groups (P < .05), except for the values at the 90° position in arthrometer measurements (P = .844). The amount of anterior translation decreased in both arthrometer measurements and stress radiography between 30° and 45° positions (P < .000); however, no further decrease was observed beyond 45°. The AUC of stress radiography at the 30° position was significantly higher than other values (AUC = 0.955; P = .000). Moreover, the clinical cutoff value of 3 mm showed 86.0% sensitivity and 89.2% specificity in stress radiography at 30°, which were higher than those in arthrometer measurements. Combined use of stress radiography and arthrometer measurements at the 30° position showed 100% sensitivity and 59.5% specificity as a screening test. Evaluation at the 30° knee position was significantly superior to that at other positions for both stress radiography and arthrometer measurements, whereas the 90° knee flexion position was not meaningful for any measurements. Evaluation needs to be performed with a 3-mm cutoff value for stress radiography at the 30° knee position; however, combined use of stress radiography and arthrometer measurements at the 30° knee flexion can have a higher diagnostic value. Level I, diagnostic study of established criteria.